Work of Love : A Theological Reconstruction of the Communion of Saints - DeLorenzo, Leonard J. (Book collections on Project MUSE., 2017)
Leonard DeLorenzo's book addresses the idea of the communion of saints, rather than individual saints, with the conviction that what makes the saints holy and what forms them into a communion is one and the same. Work of Love investigates the issue of communication within the communio sanctorum and the fullness of Christian hope in the face of the meaning-or meaninglessness-of death.